The landscape of anthropogenic mortality: how African lions respond to spatial variation in risk - Loveridge, A; Valeix, M; Elliot, N; Macdonald, D (Wiley, 2016)
1. Demography and conservation status of many wild organisms are increasingly shaped by interactions with humans. This is particularly the case for large, wide ranging carnivores. 2. Using 206 mortality records (1999–2012) of lions in Hwange National Park, Zimbabwe, we calculated mortality rates for each source of anthropogenic mortality, modelled risk of anthropogenic mortality across the landscape accounting for time lions spent in different parts of the landscape, and assessed whether subsets of the population were more at risk. 3. Anthropogenic activities caused 88% of male and 67% of female mortalities; male mortality being dominated by trophy hunting while the sources for female mortality were more varied (snaring, retaliatory killing, hunting). 4. Landscapes of anthropogenic mortality risk revealed that communal subsistence farming areas, characterized by high risk (due to retaliatory killing) but avoided by lions, are population sinks. Trophy hunting areas and areas within protected areas bordering communal farmland, where bush-meat snaring is prevalent, form ‘ecological traps’ (or ‘attractive sinks’). 5. Lions avoided risky areas, suggesting they may make behavioural decisions based on 3perceptions of risk. Experienced adults used risky areas less and incorporated lower proportions of them in their home ranges than young individuals, suggesting that the latter may either be naïve or forced into peripheral habitats. 6. Synthesis and applications. This paper contributes to an understanding of how large carnivore populations are affected by anthropogenic mortality across the conservation landscape. This is critical to designing focussed, appropriate and cost-effective conservation management strategies. Agricultural areas are intuitively identified by conservationists a being risky for carnivores due to retaliatory or pre-emptive killing, with threats largely mitigated against by improving livestock protection. However, parts of protected areas may also form less easily identified ‘attractive sinks’ for carnivores. In particular, trophy hunting areas adjacent to national parks needs careful management to avoid damaging effects of overhunting. Law enforcement is needed to reduce the effects of bush-meat poaching on predators and other wildlife in protected areas. To be most effective, resource-limited anti-poaching activities should prioritise wildlife rich areas close to human settlement as these tend to be hotspots for bush-meat poaching.